USE OF RECRATIC RESOURCES IN BESHARIQ COUNTY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article provides information on the recreational resources and their use of the Beshariq district and focuses on the restrooms and their importance in the Beshariq district.